Perilaku Birokrasi Aparat dalam Penyelenggaraan Pelayanaan Publik di Kantor Camat Dungingi Kota Gorontalo - Siti Fawzia Nurhayati W. Hippy; Arifin Tahir; Rusli Isa (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2026)
This study aims to describe the bureaucratic behavior of government officials in the implementation of public services at the Dungingi District Office, Gorontalo City, as viewed through the indicators of compliance, work diligence, responsibility, job satisfaction, and discipline. A qualitative approach was employed, with data collected through interviews, observations, and documentation.The findings indicate that, in general, the bureaucratic behavior of government officials has been fairly good, although it has not yet reached an optimal level. In terms of compliance, officials have understood and carried out their duties in accordance with established Standard Operating Procedures (SOPs), despite challenges in effectively disseminating information to the public. Regarding work diligence, officials have demonstrated efforts to complete tasks thoroughly; however, delays still occur due to attendance issues and coordination constraints. Concerning responsibility, officials have shown commitment to fulfilling their duties, although some public service processes could not always be completed within a single service period. In terms of job satisfaction, officials have exhibited a positive work attitude and motivation, but these are influenced by limitations in facilities and infrastructure. Meanwhile, regarding discipline, officials have attempted to comply with workplace regulations, yet consistency remains inadequate, particularly when supervisory oversight is reduced.Therefore, improvements are needed in employee discipline, work consistency, managerial supervision, and the provision of adequate facilities and infrastructure to enhance the quality of public services that are more effective, efficient, and oriented toward community satisfaction.